2022
DOI: 10.3390/molecules27103131
|View full text |Cite
|
Sign up to set email alerts
|

Mucuna pruriens Seed Aqueous Extract Improved Neuroprotective and Acetylcholinesterase Inhibitory Effects Compared with Synthetic L-Dopa

Abstract: L-dopa, a dopaminergic agonist, is the gold standard for the treatment of Parkinson’s disease. However, due to the long-term toxicity and adverse effects of using L-dopa as the first-line therapy for Parkinson’s disease, a search for alternative medications is an important current challenge. Traditional Ayurvedic medicine has suggested the use of Mucuna pruriens Linn. (Fabaceae) as an anti-Parkinson’s agent. The present study aimed to quantify the amount of L-dopa in M. pruriens seed extract by HPLC analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…25 Various studies have reported the presence of phenolics, flavonoids, and anthraquinones in the A racemosus, M pruriens, A pyrethrum, and T terrestris used to prepare the PHP as a trweatment of liver injury in current study. [26][27][28][29][30][31] The presence of these phytochemicals with proven antioxidant potential are responsible for the reversal of liver injury in current study. 32 Kidneys play a vital role in the excretion of toxins such as creatinine, uric acid, and urea.…”
Section: Discussionmentioning
confidence: 99%
“…25 Various studies have reported the presence of phenolics, flavonoids, and anthraquinones in the A racemosus, M pruriens, A pyrethrum, and T terrestris used to prepare the PHP as a trweatment of liver injury in current study. [26][27][28][29][30][31] The presence of these phytochemicals with proven antioxidant potential are responsible for the reversal of liver injury in current study. 32 Kidneys play a vital role in the excretion of toxins such as creatinine, uric acid, and urea.…”
Section: Discussionmentioning
confidence: 99%
“…Mucuna pruriens ( M. pruriens ), routinely known as Mucuna or velvet bean, is a popular medicinal plant belonging to the legume family and common in tropical and subtropical areas worldwide. In India, it is widely found in the eastern part of the country ( Kamkaen et al, 2022 ). Several studies have reported the anti-Parkinson, antidiabetic, antioxidant, antibacterial, antiepileptic, antineoplastic, male fertility, and aphrodisiac effects of M. pruriens ( Rane et al, 2019 ; Theansungnoen et al, 2022 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical analysis of M. pruriens seed extract has demonstrated a significant content of L-dopa accounting for its anti-parkinsonism properties. It has been widely used in Ayurveda as a medicinal plant since Vedic times and is used to treat various nervous disorders, probably due to its neuroprotective properties ( Rane et al, 2019 ; Kamkaen et al, 2022 ). Hence, the primary objective of the present work was to study the possible neuroprotective effect of pretreatment with M. pruriens seed extract and its isolated bioactive molecule(s) in the cerebral ischemic rat model and its impact on NMDA receptor and Tau protein gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…Mucuna pruriens ( M. pruriens ) is a tropical legume in Fabaceae family. Mucuna seed contains abundant natural L-dopa, which has been shown to be more tolerated and more potent than synthetic L-dopa [ 1 , 2 , 3 ]. Pre-clinical and clinical studies have shown that M. pruriens seed containing natural L-dopa had benefits over synthetic L-dopa in terms of higher efficacy and lower adverse effect.…”
Section: Introductionmentioning
confidence: 99%